Aspek Determinan Pemilihan Penolong Persalinan di Wilayah Kerja Puskesmas Rancabungur - ida nuraida (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2022)
The maternal Mortality Rate is one indicator of development in the health sector. Maternal mortality during childbirth is estimated to be almost one mother every minute who dies due to pregnancy and childbirth. The purpose of this study was to determine the relationship between the determinants of the selection of birth attendants in the working area of the Rancabungur Health Center. This study used a cross-sectional design, where a sample of 148 respondents using the Accidental Sampling technique was analyzed using chi-square. The results of bivariate data analysis of the variables (knowledge, attitudes, distance from home, family income, husband's support, support for health workers, and support for cadres) have a relationship with the selection of birth attendants (p-value < 0.05). Conduct counseling activities about pregnancy and childbirth to community leaders and religious leaders to participate in supporting the increase in birth attendants by health workers.